Significado laboratorial dos baixos títulos de VDRL para o diagnóstico da sífilis em gestantes: à luz das provas treponêmicas - Campos, Jose Eduardo B.; Passos, Felipe D.L.; Ferreira, Antônio Walter; Sá, Carlos Alberto M.; Silva, Luiz, Guilherme P.; Asensi, Marise D. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: the best prevention for congenital syphilis is possibly doing the serological tests during the prenatal period, mainly in the women with risky behavior for the HIV or STD infections. For the physician, the importance of this illness exceeds its clinical aspects, because of the vertical transmission of its etiological agent. In such a way, the early and correct laboratorial diagnosis is a powerful tool in the prophylaxis of the congenital syphilis. Objective: best interpreting and understanding low titles of VDRL in pregnancy. Methods: 215 samples of pregnant women’s serum from two maternities in Rio de Janeiro, RJ were analyzed. The VDRL test and treponemal tests (TPHA, ELISA and Western-blotting) were used. The titles of VDRL were confronted with no-reagents tests, as independent variables to confirm tests. Results: by means of the comparative analysis of sensibi lity and specificity of the tests, the ROC {Receiver Operator Characteristic) curve was attained. The overall accuracy of the sundry techniques used in the study showed that the VDRL titles above 1/1 associate significantly with the treponemal tests. The results of VDRL expressed by low titles, mainly in titrations above 1/1 revealed significant association with the confirmatory tests of syphilis. Conclusion: the results show that the low titles of VDRL should be valued and that the test considered as a screening test, may also be useful when employed as a diagnosis test for syphilis in preg nant women.